Introduction of a new Indo-Pacific marine cladoceran to the Mediterranean Sea - TERBIYIK KURT, TUBA; POLAT, SEVIM (Mediterranean Marine Science, 2018)
Pleopis schmackeri, a podonid cladoceran not previously recorded in the Mediterranean Sea, was found in the İskenderun Bay for the first time. The samples were collected seasonally during 2012–2015 in the coastal area of İskenderun Bay using a WP-2 zooplankton net (200 µm). Six cladoceran species were found in total, and Penilia avirostris, Pseudevadne tergestina and Evadne spinifera constituted the bulk of the population, while the contribution of P. schmackeri was very low. Although only a single individual was observed in July 2012, the abundance and frequency of P. schmackeri increased in the following years, attaining the abundance of 25.10 ind.m-3 in 2015. Thus, P. schmackeri could be considered as established in İskenderun Bay; however, it seems that it did not affect the distribution of other cladoceran species in the area up to now. P. schmackeri could have entered in İskenderun Bay either as Lessepsian migrant or by ballast waters of commercial ships.